The effect of intra-articular injection of autologous bone marrow stem cells on pain and knee function in patients with osteoarthritis - Garay Mendoza, Domingo; Villarreal Martínez, Laura; Garza Bedolla, Alejandra; Pérez Garza, Daniela Michelle; Acosta Olivo, Carlos Alberto; Vílchez Cavazos, José Félix; Diaz Hutchinson, Cesar; Gómez Almaguer, David; Jaime Pérez, José Carlos; Mancías Guerra, María del Consuelo (2017)
Abstract Aim: Management of osteoarthritis (OA) is basically symptomatic. Recently, stem cells (SC) have been used in the search for an optimum treatment. We decided to conduct a controlled clinical trial to determine if a single intra-articular injection of in vivo stimulated bone marrow SC could lead to an improvement in pain management and quality of life in patients with knee OA. Method: This was a prospective, open-label, phase I/II clinical trial to assess the safety and efﬁcacy of a single intra-articular injection of autologous stimulated bone marrow stem cells (BM-SC) in patients with knee OA. Individuals of both genders older than 30 years with conﬁrmed diagnosis of OA who signed informed consent were included in two groups: SC group received in vivo BM stimulation with subcutaneous administration of granulocyte colony stimulating factor (G-CSF). SC were obtained by BM aspiration and administered in a single intra-articular injection. The control group received exclusively oral acetaminophen. Visual analogue scale and Western Ontario and McMaster Universities Osteoarthritis Index scores were performed at 1 week, 1 month and 6 months in both groups. This trial was registered in ClinialTrials.gov NCT01485198. Results: A total of 61 patients were included. Socio-demographic characteristics, OA grades and initial scores were similar in both groups. The BM-SC group showed signiﬁcant improvement in knee pain and quality of life during the 6-month follow-up. Conclusion: The study demonstrates feasibility and supports efﬁcacy of a completely ambulatory procedure in treatment of knee OA. Key words: bone marrow, knee osteoarthritis, stem cells.